PERANCANGAN DAN PEMBUATAN ARIT PEMOTONG RUMPUT SEDERHANA DI DESA PADAKATON KABUPATEN BREBES - M Munawir Lasiyono (Journal of Innovation Research and Knowledge, 2021)
This study discusses the design and manufacture of simple grass cutter sickles, while the benefits are useful for helping grass seekers during the process of cutting grass who have been using sickles as a traditional lawn mower to make it more comfortable to use. Simple grass cutter sickle consists of several components, namely iron and wood, Design for the main frame using steel, Supporting applications in making product shape design using software inventor so that images of the product are obtained. The fabrication process is carried out in the workshop until the sickle is ready in a shape according to the design in the drawing. After the tool is complete, the next step is the testing phase. The testing phase was carried out in paddy fields. The parameter to be observed is the comfort of using the sickle.